Penerapan Business Model Canvas pada UMKM Tahu Tempe Mandiri Jaya di Kelurahan Girian Bawah Kecamatan Girian Kota Bitung - Haurani Kammila; Barce Andries Feriano Wariki; Melsje Yellie Memah (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the community's economy, especially in the food industry sector. One of the growing businesses is the Mandiri Jaya tofu and tempe industry located in Girian Bawah Village, Girian District, Bitung City. This study aims to identify the business model of the industry using the Business Model Canvas (BMC) approach. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The analysis is based on nine BMC elements: customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. The results show that the main customer segments include housewives, market traders, food stalls, and fried food vendors. The main value proposition offered is fresh, high-quality tofu and tempe products with larger sizes and affordable prices. Distribution channels are carried out through direct sales, traditional markets, and regular distributors. Customer relationships are maintained through personal communication and good service. The application of the Business Model Canvas helps business owners understand their business structure and identify opportunities for business development to remain competitive in the market.